Does implementation of competence-based education mediate the impact of team learning on student satisfaction?. (1st October 2020) - van Griethuijsen, Ralf A.L.F.; Kunst, Eva M.; van Woerkom, Marianne; Wesselink, Renate; Poell, Rob F.
ABSTRACT: Competence-based education (CBE) is an innovation in (vocational) education aimed at improving students' competences. Little is known, however, about the processes leading to successful implementation of CBE and about its outcomes. This study investigates the effects that the level of CBE implementation has on student satisfaction (regarding the quality of education, guidance, and the development of interpersonal and general vocational skills) and to what extent CBE implementation mediates the relationship between teacher team learning activities and student satisfaction. To this end, data was gathered from 662 teachers belonging to 46 teacher teams in senior secondary vocational education in the Netherlands, and their students. Multilevel structural equation modelling revealed that teacher team learning was positively associated with te implementation of CBE. Furthermore, CBE had a positive effect on student satisfaction with quality of education, guidance, and development of interpersonal skills; however, no significant effect was found on student satisfaction with the development of general vocational skills. These results indicate that implementation of CBE has, to some degree, fulfilled its promise of better preparing students for their future workplace and that teacher team learning can support the further implementation of CBE. Abbreviation : CBE – Competence-based education